Single halide perovskite/semiconductor core/shell quantum dots with ultrastability and nonblinking properties - Tang, Xiaosheng (2019)
The further practical applications of halide perovskite quantum dots (QDs) are blocked by problems of instability and nonradiative Auger recombination manifested as photoluminescence blinking. Here, single core/shell structured perovskite semiconductor QDs are successfully fabricated by capping CsPbBr3 QD core with CdS shell. It is demonstrated that CsPbBr3/CdS core/shell QDs exhibit ultrahigh chemical stability and nonblinking photoluminescence with high quantum yield due to the reduced electronic traps within the core/shell structure. Efficiency of amplified spontaneous emission exhibits obvious enhancement compared to that of pure CsPbBr3 QDs, originating from the mitigated competition between stimulated emission and suppressed nonradiative biexciton Auger recombination. Furthermore, low‐threshold whispering‐gallery‐mode lasing with a high‐quality factor is achieved by incorporating CsPbBr3/CdS QDs into microtubule resonators. Density functional theory (DFT)‐based first‐principles calculations are also performed to reveal the atomic interface structure, which supports the existence of CsPbBr3/CdS structure. An interesting feature of spatially separated charge density at CsPbBr3/CdS interface is found, which may greatly contribute to the suppressed Auger recombination. The results provide a practical approach to improve the stability and suppress the blinking of halide perovskite QDs, which may pave the way for future applications for various optoelectronic devices.